2020
DOI: 10.1111/1759-7714.13680
|View full text |Cite
|
Sign up to set email alerts
|

Video‐assisted thoracoscopic surgery lobectomy might be a feasible alternative for surgically resectable pathological N2 non‐small cell lung cancer patients

Abstract: Background: The majority of previous studies of the clinical outcome of videoassisted thoracoscopic surgery (VATS) versus open lobectomy for pathological N2 non-small cell lung cancer (pN2 NSCLC) have been single-center experiences with small patient numbers. The aim of this study was therefore to investigate these procedures but in a large cohort of Chinese patients with pathological N2 NSCLC in real-world conditions. Methods: Patients who underwent lobectomy for pN2 NSCLC by either VATS or thoracotomy were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…For NSCLC patients with mediastinal lymph node metastasis, several factors including inadequate experience during training, 35 narrow visual field with limited range of instrumental movement, 36 and inferior oncological effectiveness (e.g., lymph node assessment) may contribute to the major concerns of VATS for pN2 NSCLC. 21,37 However, Li et al 26 performed a retrospective analysis of 76 patients comparing clinical outcomes for patients with clinical N0, but pathologic N2 NSCLC patients after VATS lobectomy and thoracotomy lobectomy, they F I G U R E 4 Forest plot of (a) 1-year OS, and (b) 3-year OS; PSM, propensity score matched; VATS, video-assisted thoracoscopic surgery; OS, overall survival; CI, confidence interval found that VATS approach could yield similar total number of dissected mediastinal lymph node and the total number of dissected lymph node stations. Zhong et al 10 also found the similar result that VATS approach was effective in lymph node dissection compared with thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For NSCLC patients with mediastinal lymph node metastasis, several factors including inadequate experience during training, 35 narrow visual field with limited range of instrumental movement, 36 and inferior oncological effectiveness (e.g., lymph node assessment) may contribute to the major concerns of VATS for pN2 NSCLC. 21,37 However, Li et al 26 performed a retrospective analysis of 76 patients comparing clinical outcomes for patients with clinical N0, but pathologic N2 NSCLC patients after VATS lobectomy and thoracotomy lobectomy, they F I G U R E 4 Forest plot of (a) 1-year OS, and (b) 3-year OS; PSM, propensity score matched; VATS, video-assisted thoracoscopic surgery; OS, overall survival; CI, confidence interval found that VATS approach could yield similar total number of dissected mediastinal lymph node and the total number of dissected lymph node stations. Zhong et al 10 also found the similar result that VATS approach was effective in lymph node dissection compared with thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies reported the results of operation time, blood loss and complication rate. 10,14,[20][21][22][25][26][27] The results showed that VATS for NSCLC patients with pN2 disease yielded significantly less blood loss (WMD, À61.43; 95% CI, [À87.69, À35.18]; p < 0.001) than those receiving thoracotomy (Figure 2(a)). Moreover, VATS surgery could yield comparable operation time (WMD, À8.32; 95% CI, [À23.88, 7.23]; p = 0.29) and post-operation complication rate (RR, 0.95; 95% CI, [0.78, 1.15]; p = 0.59) to thoracotomy (Figure 2(b), (c)).…”
Section: Comparison Of Short-term Outcomes Between Vats Group and Tho...mentioning
confidence: 99%
See 3 more Smart Citations